Study on the Transmission Characteristic of Concentric Permanent Magnetic Planetary System - Wang Peng; Zhou Kaikai; Yuan Zhi; Yang Junyue; Ge Yanjun (Jixie chuandong)
Based on energy approach and finite element simulation software,theoretical analysis and finite element verification are carried out for Concentric permanent magnetic planetary Gear（ CPMPG）. Through designing the model parameters of CPMPG,analyzing the magnetic density in air gap and calculating the overall transmission ratio and torque,the proposed CPMPG structure can effectively improve the transmission ratio of the concentric permanent magnetic gear. Although the dynamic torque density of the proposed structure is slightly lower than the static torque density,it is still much higher than the permanent magnetic motor,which verifies the validity and practicability of the proposed structure.